Cloning and expression characterisation of LiDXS2 gene in Oriental Lily (Lilium 'Sorbonne') - Yu Jiaxuan; Wu Nana; Fu Ruyu; Xue Lili; Zhang Jinzhu; Dong Jie; Yang Tao; Fan Jinping (Folia Horticulturae)
1-Deoxy-D-xylulose-5-phosphate synthase (DXS) is the first key enzyme in the MEP responsible for monoterpene synthesis. To reveal its regulatory effect on floral scents of lily, LiDXS2 was cloned from Oriental Lily ‘Sorbonne’; the protein location was determined using subcellular localisation; and the expression pattern in different flowering stages and tissues was probed by fluorescence quantitative PCR. The plant expression vector was constructed to transform Arabidopsis thaliana, and the transgenic plants were characterised. The results showed that the LiDXS2 ORF area was 2142 bp and encoded a total of 713 amino acids. Analysis of homologous sequences showed that it contains two highly conserved regions, WDVGHQ and IAEQHA, which were closely related to Ginkgo DXS2 protein and Periwinkle DXS protein. Subcellular localisation showed that the LiDXS2 gene of Lilium 'Sorbonne' was localised in chloroplasts. In different flowering stages, the expression patterns of LiDXS2 were basically the same as the TranScriptome sequencing results, and the overall trend was initially increasing and then decreasing. In different floral organ tissues, the expression level of LiDXS2 was significantly higher in petals than other tissues, and almost no expression was observed in anthers. In A. thaliana transformed by LiDXS2, the transgenic lines showed an increased plant height and early flowering phenotype, and the expression of volatile synthesis genes for key structures downstream of DXS in the MEP pathway was upregulated compared with controls. Collectively, these results suggest that LiDXS2 may play an important role in regulating Lilium ‘Sorbonne’ monoterpene synthesis and its floral flavour release.